The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1155/2019/9019253
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Hypoxia Responsive microRNAs (HRMs) and Wound Healing Potentials of Green Tea in Diabetic and Nondiabetic Rat Models

Abstract: Green tea (Camellia sinensis) has many biological activities and may promote diabetic wound healing by regulation of circulating hypoxia responsive microRNAs (HRMs) which triggers the wound repairing process in diabetic and nondiabetic wounds. Thus, in this study, the potential effects of green tea extract (GTE) on the expression of miRNAs; miR-424, miR-199a, miR-210, miR-21, and fibrogenitic markers; hydroxyproline (HPX), fibronectin (FN), and nitric oxide (NO) were evaluated in wounds of diabetic and nondiab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 110 publications
1
13
0
Order By: Relevance
“…In addition, miR-21 mimic MVs augmented the endotheliocyte angiogenic activity and promoted the fibroblast differentiation compared to miR-21 inhibitor MVs and vector MVs ( Li et al, 2019 ). This is consistent with a previous study ( Al-Rawaf et al, 2019 ). The in vivo studies demonstrated that treatment with miR-21 mimic MVs significantly accelerated wound healing compared to treatments with vector MVs and miR-21 inhibitor MVs ( Li et al, 2019 ).…”
Section: Overview Of Mir-21supporting
confidence: 94%
“…In addition, miR-21 mimic MVs augmented the endotheliocyte angiogenic activity and promoted the fibroblast differentiation compared to miR-21 inhibitor MVs and vector MVs ( Li et al, 2019 ). This is consistent with a previous study ( Al-Rawaf et al, 2019 ). The in vivo studies demonstrated that treatment with miR-21 mimic MVs significantly accelerated wound healing compared to treatments with vector MVs and miR-21 inhibitor MVs ( Li et al, 2019 ).…”
Section: Overview Of Mir-21supporting
confidence: 94%
“…Based on the cause, wounds can be classified as an incision, crush, laceration, and perforation, without tissue loss, or wounds with tissue loss. [8,9] Many biological particles, molecules, and different cell types have a part that is involved during all the wound healing phases. Besides, hemostasis, inflammation, cell proliferation, re-epithelialization, and remodeling are in succession take placed in the phases of normal wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, hemostasis, inflammation, cell proliferation, re-epithelialization, and remodeling are in succession take placed in the phases of normal wound healing. [9,10] In the literature, there are many studies revealing new therapeutic approaches or molecular-based recovery period to overcome the difficulty and slow healing processes of chronic wounds, such as diabetic foot, decubitus, and venous leg ulcer. [9,[11][12][13][14][15] In clinical practice, to patients with a cutaneous wound, systemic drugs as orally and parenterally can be administered; however, this may result in the development of several side effects limiting their long-term use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations